Pengaruh Prinsip Good Corporate Governance Terhadap Ketepatan Waktu Pelaporan Keuangan Pada AJB Bumiputera 1912 Cabang Samrat Manado - Salindeho, Doan; Tampi, Dolina L.; Manoppo, Wilfried S. (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
This study aims to determine whether the GCG principles influence and play an active role and work efficiently to the timeliness of financial reporting. The type of research used in this study is descriptive qualitative research with descriptive data analysis techniques and data collection methods used are interviews and document studies. From the results of interviews to 4 informants who are employees AJB Bumiputera 1912 Branch Samrat Manado and document studies of these companies hence this study shows that the GCG principles influence and play an active role and work efficiently on AJB Bumiputera 1912 Branch Samrat Manado with the timeliness of financial reporting at the company . From the analysis of the study document company shows that AJB Bumiputera 1912 Branch Samrat Manado reported financial reporting in a timely manner by emphasizing the principles of Good Corporate Governance in it. Based on the results of research and discussion in this study it can be concluded that, from the results of interviews with researchers and informants document research company showed that the principles of Good Corporate Governance influence and play an active and efficient role in AJB Bumiputera 1912 Branch Samrat Manado, with the timeliness of financial reporting on the company. Furthermore, interviews with informants show that transparency, accountability and responsibility have a greater influence on the timeliness of financial reporting in AJB Bumiputera 1912 of Samrat Manado Branch, compared with the fairness principle, and the principle of independence that tends to have smaller roles and lesser efficiency and efficiency.Keywords: Good Corporate Governance, Timeliness of Financial Reporting